Ultrasound guided platelet rich plasma or corticosteroid for supraspinatus tendonosis or partial tear: an observational study of clinical outcome - Dasgupta, Tirthankar; Das, Mainak; Gogia, Tushar; Singh, Narender; Tiwary, Aashish; Verma, Vaibhav (International Journal of Research in Orthopaedics, 2023)
Background: The clinical application of platelet rich plasma (PRP) in rotator cuff tears has increased recently. Many studies have found no difference between placebo controls and PRP and corticosteroids (CS) and some have found more rapid benefits with PRP injections. The present study was undertaken with the objectives to observe and assess efficacies of the two different treatment modalities in terms of symptomatic relief and recovery of ROM and to ascertain the duration of symptom free period and functional improvement on follow up. Methods: Observational clinical outcome study, conducted at a tertiary care hospital between September 2020 and March 2022 after institute ethical committee clearance. A total of 100 patients, with a positive clinical test for supraspinatus and magnetic resonance imaging (MRI) suggestive of supraspinatus tendinitis were divided to 2 groups and based on whether they received either intra-articular CS or PRP injection under ultrasonography (USG) guidance All patients were followed up at for assessing the outcomes at 6 weeks, 3 months and 6 months from intervention Results: The clinical outcome of the group receiving the PRP was better than group receiving CS intervention. Conclusions: PRP should therefore be considered as a viable option to treat supraspinatus tendinopathy/partial tear as it is cheap, readily available modality using patients own blood which is more acceptable to patient and also safe to individual where complications related to corticosteroids anticipated. Ultrasound guided procedure were found to enhance the accuracy of injection.